New reference values for ultrasound fetal biometry in Japanese population and comparison with other studies - Sumito Nagasaki; Keisuke Ishii; Yoshitaka Murakami; Anna Tsutsui; Nobuhiro Hidaka; Hironori Takahashi; Kiyotake Ichizuka; Kei Miyakoshi; Kiyonori Miura; Susumu Miyashita; Yoshimasa Kamei; Masahiko Nakata; et al. (Scientific Reports)
Abstract Given the decline in birthweights over the past 30 years in Japan and advancements in ultrasound technology, this study aimed to establish new reference values for ultrasound fetal biometry in Japan and to compare them with international and Asian studies. We conducted a cross-sectional prospective study involving singleton pregnancies who received prenatal checkups at obstetric facilities across Japan. During routine prenatal care, ultrasound measurements—biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), and femur length (FL)—were recorded. Estimated fetal weight (EFW) was calculated using both the Shinozuka formula, commonly used in Japan, and the Hadlock-3 formula, widely used internationally. Using the collected data, we developed gestational-age-specific reference values for BPD, HC, AC, FL, and EFW by applying best-fitted fractional polynomial regression, and compared them with existing international standards and reference values from other Asian countries. The mean EFW calculated by the Hadlock formula in this study tended to be smaller than that reported in other international studies, and BPD, HC, AC, and FL were also generally smaller than those observed in other Asian references. These findings indicate that fetal biometry values in the Japanese population are smaller not only than international standards but also compared with those from other Asian countries, and suggest that these population-specific data may contribute to improving the accuracy of fetal growth assessment in Japan and other parts of Asia.